Lessons From Rojava for the Paradigm of Social Ecology - Hammy, Cihad; Miley, Thomas Jeffrey (Frontiers in Political Science, 2022)
This essay addresses two related questions raised by the editors of the research topic for “Beyond the Frontiers of Political Science: Is Good Governance Possible in Cataclysmic Times?” In particular, it explores: (1) how we can identify new tools and perspectives from which to address the multiple and mutually reinforcing problems accumulating around climate change; and (2) what institutional alternatives to the nation-state need to be created and empowered to tackle such complex problems. It does so through an in-depth treatment of the paradigm of “social ecology” and the associated political project of “democratic confederalism.” It begins with an overview of the argument, first advanced by Murray Bookchin and subsequently adopted and adapted by the imprisoned Kurdish leader Abdullah Öcalan, that building an ecological society requires an assault on hierarchy in all its forms, and the construction of alternative, direct-democratic institutions capable of transcending the system of the capitalist nation-state. It sketches the institutional architecture of popular assemblies central to this project, both emphasizing their potential to contest capitalist social-property relations and hierarchies intrinsic to the nation-state and pointing out some sources of resilience of the existing system. It hones in on the experience of the revolutionary forces in control of the Autonomous Administration of North East Syria (AANES), who have been directly inspired by Öcalan’s ideas. It highlights both the AANES’s achievements as well as the significant obstacles it has encountered in the attempt to bring into being a radically-egalitarian, ecological society. It concludes by drawing lessons from these difficulties.